Retrospective Investigation of the Utility of Potassium Hydroxide Smear in the Diagnosis and Management of Cutaneous Fungal Infections by Dermatologists - Xuan Qi Koh; Huirong Han; Liang Shen; Nisha S. Chandran (Indian Journal of Dermatology, 2024)
Background Superficial cutaneous fungal infections are common dermatologic conditions. A significant proportion do not present with typical clinical findings. However, the 10% potassium hydroxide (KOH) smear, a simple bedside test, is often underused when diagnosing cutaneous fungal infections. Aims We aimed to evaluate whether KOH smear results altered dermatologists’ diagnosis and management, and the factors that influenced its ability to detect cutaneous fungal infections. Methods A total of 373 patients with suspected cutaneous fungal infection were identified retrospectively from the dermatology database of inpatient referrals in a Singapore tertiary hospital between 1 January 2017 and 30 June 2020. The dermatologists’ eventual diagnoses, based on their assessment until 2 months post-discharge to allow consideration of KOH smear results and response to treatment, were taken as a gold standard. Statistical analyses evaluated for changes between initial and eventual diagnoses and management relative to the KOH smear. Use of topical steroids, topical and/or systemic antifungals before skin sampling, and whether sampling was done by dermatologically-trained personnel, were assessed for association with KOH smear positivity in eventually diagnosed cases. Results The percentage of uncertain diagnoses was reduced, and the use of topical antifungal as the sole treatment significantly changed after the KOH smear result was available. The adjusted odds ratio of a positive KOH smear in eventually diagnosed cases was 0.19 when systemic antifungals were used before skin sampling, and 3.03 if sampling was performed by a dermatologically-trained person. Limitations Limitations of our study include dependence on retrospective medical records which may result in misclassification bias and the limited generalisability of our results to patients managed by non-dermatologists. Conclusions KOH smear is a useful adjunct in diagnosing and managing cutaneous fungal infections. Clinicians should consider the presence of confounders affecting KOH smears when making an overall clinical diagnosis. Focused training of personnel on skin sample collection may improve the detection rate of KOH smear.